2006
DOI: 10.1364/ao.45.001072
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo-based inverse model for calculating tissue optical properties Part II: Application to breast cancer diagnosis

Abstract: The Monte Carlo-based inverse model of diffuse reflectance described in part I of this pair of companion papers was applied to the diffuse reflectance spectra of a set of 17 malignant and 24 normal-benign ex vivo human breast tissue samples. This model allows extraction of physically meaningful tissue parameters, which include the concentration of absorbers and the size and density of scatterers present in tissue. It was assumed that intrinsic absorption could be attributed to oxygenated and deoxygenated hemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
119
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 23 publications
6
119
1
1
Order By: Relevance
“…35 The hemoglobin saturation showed a significant decrease in malignant tissues relative to that in nonmalignant (including both fibrous/benign and adipose) tissues (p<0.0001), which is likely due to the oxygen extraction of rapidly proliferating tumor cells. This property agreed with the findings from our previous studies, 17,18 and has also been reported in several previous studies using other techniques such as pO 2 measurements 36,37 and near-IR (NIR) diffuse optical spectroscopy. 33,38,39 Malignant breast tissues had an increased mean reduced scattering coefficient compared to that of nonmalignant breast tissues, which is also consistent with the findings from earlier studies published by Peters et al 14 and Ghosh et al 16 Three fluorescence components were extracted from the MCR analysis of the intrinsic fluorescence spectra.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…35 The hemoglobin saturation showed a significant decrease in malignant tissues relative to that in nonmalignant (including both fibrous/benign and adipose) tissues (p<0.0001), which is likely due to the oxygen extraction of rapidly proliferating tumor cells. This property agreed with the findings from our previous studies, 17,18 and has also been reported in several previous studies using other techniques such as pO 2 measurements 36,37 and near-IR (NIR) diffuse optical spectroscopy. 33,38,39 Malignant breast tissues had an increased mean reduced scattering coefficient compared to that of nonmalignant breast tissues, which is also consistent with the findings from earlier studies published by Peters et al 14 and Ghosh et al 16 Three fluorescence components were extracted from the MCR analysis of the intrinsic fluorescence spectra.…”
Section: Discussionsupporting
confidence: 93%
“…This work is distinct from previous publications by our group 5,17,18 in that first, it reports on the application of a new fluorescence model to recover the intrinsic fluorescence and then extract the contributions of individual fluorescing components that may relate to intrinsic fluorophores in the breast; second, it compares the merits of the extracted fluorescence properties versus the tissue absorption and scattering properties for diagnosing breast cancer; and finally, it demonstrates the consistency of our model-based approach for the analysis of diagnostically useful information contained in fluorescence and diffuse reflectance spectra measured with two different instruments and probe geometries.…”
Section: Introductioncontrasting
confidence: 72%
See 3 more Smart Citations